In vivo analysis of cadmium in battery workers versus measurements of blood, urine, and workplace air. Issue 6 (June 1997) - Börjesson, J; Bellander, T; Järup, L; Elinder, C G; Mattsson, S
Abstract : OBJECTIVES: To measure in vivo the cadmium concentrations in kidney cortex (kidney-Cd) and in superficial liver tissue (liver-Cd) of nickel cadmium battery workers, and to compare the results with other commonly used estimates of cadmium exposure (current concentrations of cadmium in blood (B-Cd) and urine (U-Cd)) or repeated measurements of cadmium in workplace air (CumAir-Cd). METHODS: The study comprised 30 workers with a range of duration of exposure of 11-51 years. 13 subjects were currently employed, whereas the other 17 had a median period without occupational exposure of eight years before the measurements. The in vivo measurements were made with an x ray fluorescence technique permitting average detection limits of 30 and 3 micrograms cadmium per g tissue in kidney and liver, respectively. RESULTS: 19 of 30 (63%) people had kidney-Cd and 13 of 27 (48%) had liver-Cd above the detection limits. Kidney-Cd ranged from non-detectable to 350 micrograms/g and liver-Cd from non-detectable to 80 micrograms/g. The median kidney-Cd and liver-Cd were 55 micrograms/g and 3 micrograms/g, respectively. Kidney-Cd correlated significantly with B-Cd (r, 0.49) and U-Cd (r, 0.70), whereas liver-Cd correlated significantly with U-Cd (r, 0.58). Neither kidney-Cd nor liver-Cd correlated with the CumAir-Cd. The prevalence of beta 2-microglobulinurea increased with increased liver-Cd. CONCLUSIONS: Current U-Cd can be used to predict the kidney-Cd and liver-Cd measured in vivo. In vivo measurements of kidney-Cd and liver-Cd were not shown to correlate with the individual cadmium exposure estimates, obtained by integration of the cadmium concentration in workplace air. There may be several reasons for this, including uncertainties in the estimate of the individual cumulative exposures as well as in the in vivo measurements. There was a suggestion of a relation between liver-Cd and tubular proteinuria.